Empirical and Theoretical Study of the Thermal Performance of High Power Uvc Leds - Soto-Ormeno, C (Optica Publishing Group (formerly OSA), 2022)
UVC LEDs exhibit high junction temperature (TJ) and voltage sensitivity, which influences their radiant power and lifetimes. This study of 275nm, 3-PAD UVC LEDs can be useful to estimate TJ and emphasize the need for optimal thermal management. © Optica Publishing Group 2022.